KORELASI KETEPATAN PENCATATAN TERMINOLOGI MEDIS DAN KEAKURATAN KODE DIAGNOSIS MORBIDITAS RESPIRASI DI RUMAH SAKIT MUSLIMAT MALANG : Correlation Between Coincidentally Recording Medical Terminology and Accuracy of Respiratory Morbidity Diagnosis Code in Muslimat Hospital Malang - Untung Slamet Suhariyono; Retno Dewi Prisusanti; Achmad Jaelani Rusdi (Forind Press, 2023)
Based on Permenkes No. 55 of 2013 concerning the Implementation of Medical Recorder Work states that coding patient diagnoses must be carried out by medical record officers who have competence related to disease classification and codification. This research method is quantitative with a cross-sectional approach. The research variables are medical terminology accuracy and diagnosis coding accuracy. The sample for this study consists of outpatient medical records for respiratory diseases in December 2022 at Muslimat Singosari Hospital in Malang. The results of this research showed that the accuracy of medical terminology based on the use of terms is 81%, the accuracy of medical terminology based on the use of abbreviations is 83%, and the accuracy of respiratory disease diagnosis code is 80.3%. Based on the Chi-Squared test results, the p-value is 0.042. Therefore, with a p-value of 0.042 < alpha value of 0.05, it is interpreted that H0 (null hypothesis) is rejected and H1 (alternative hypothesis) is accepted, indicating a relationship between the accuracy of medical terminology and the accuracy of respiratory disease diagnosis codes at Muslimat Singosari Hospital in Malang. The suggestions to consider include standardizing or establishing medical terminology in accordance with ICD-10 and the Dorland's dictionary, implementing clearer regulations regarding reference guidelines for diagnosis coding to minimize inaccuracies in diagnosis codes, and appointing employees with relevant medical record qualifications to their respective roles.